Key Success Factor of Social Entrepreneur’s Business in the New Normal Era: Systematic Literature Review - Ni Wayan Bella Astika Dewi; Ida Bagus Raka Suardana; Luh Putu Mahyuni; Ida Ayu Oka Martini (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Social entrepreneurship has emerged as an innovative approach to addressing complex social problems while generating sustainable social value. Therefore, this study aimed to identify the key success factors of social entrepreneurship by synthesizing existing evidence on social entrepreneurs’ motivation, traits, and challenges. A Systematic Literature Review (SLR) was conducted following a structured process of identification, screening, eligibility assessment, and qualitative synthesis. Relevant articles were retrieved from ScienceDirect, Emerald Insight, Taylor & Francis, and Google Scholar through the Publish or Perish application. Of the 669 articles initially identified, 45 met the inclusion criteria and were included in the final analysis. The findings revealed three major themes influencing social entrepreneurship success: social entrepreneurs’ motivation, social entrepreneurs’ traits, and social entrepreneurs’ challenges. Self-efficacy and empathy emerged as the dominant motivational factors, whereas agreeableness, extraversion, and openness to experience represented the most influential entrepreneurial traits. Meanwhile, financial constraints, limited human resources, inadequate institutional support, and technological adaptation constituted the primary challenges. These findings suggest that the success of social entrepreneurship depends on the interaction between entrepreneurs’ internal capabilities and supportive external ecosystems, emphasizing the importance of simultaneously strengthening individual competencies and institutional support.